Understanding and Interpreting Urban Space (in)formation. (June 2013) - Verovsek, Spela; Juvancic, Matevz; Zupancic, Tadeja
This paper introduces a novel approach to understanding the complex information and logics of urban spaces by the non-professional public. A model for Interpretation of Qualities in Urban Space (aMIQUS) is proposed. The objectives are threefold: first, to form common, valid and applicable measures to assess features of space design; second, to indicate the developmental trait that considerably affect users' spatial experience which - taken as a consequence - derives from either sustainable/prudent or poor design decisions; and third, to generically recreate and visually represent urban spaces for communicative purposes. The model represents an identification method, not a problem-solving mechanism and is intended as a pragmatic instrument for recognizing crucial information, narrative, embedded in spatial scene. Model is followed by the initial idea to extend it in terms of an educational digital interface for the general public, participating in the process of urban decision-making. The paper concisely summarizes both theoretical and applicative efforts.